Productivity and Growth of Manufacturing Industries in Nepal (Economic Journal of Nepal, 2018)
This paper examines efficiencies measures including factors influencing on output, total factor productivity (TFPG) and factors affecting on TFPG of manufacturing industries of Nepal. Regression equation is estimated to find factors influencing on output and factors affecting TFPG. Extended Cobb-Douglas production function is examined to find TFPG. As it is disclosed by efficiencies measures such as labor productivity, capital productivity and material efficiency, there is not coherent relation among efficiency measures and output rather than in few cases. It implies that  output increase due to many reasons such as protection, internal demand, availability of material input, comparative advantage and so on. As it is evident by the regression result; output is mainly interrelated with the inherent components like labour, capital and material input though road is also notices as positive factor. Liberalization dummy notifies negative impact on output. Improved TFPG at post liberalization phase is realized to those years in which capital is also increased which suggests increment tin capital probably with improved technology is required to increase overall efficiencies. Capital intensity, export incentive and foreign direct investment are found as factors affecting on TFPG. This study under scores the importance of comparative advantage production since there is not coherence on productivity, growth and efficiencies measures.